Avaliação de um sistema push-pull composto por um dispositivo liberador de transflutrina e a armadilha gravid aedes trap para a supressão de adultos Aedes (Stegomyia) aegypti (Linnaeus, 1762) (Diptera: Culicidae) - Leonardo Rodrigues dos Santos (2023)
Introduction: Innovative methods that modify or prevent Aedes aegypti oviposition are extremely relevant to control this mosquito population and the spatial repellent application to inhibit the Ae. aegypti oviposition in places where it would normally occur, may represent an important addition against this vector. Objectives: 1) To evaluate effects of transfluthrin exposure on gravid Ae. aegypti and on biological parameters of their descendant’s development; 2) Develop and evaluate under semi-field and field conditions a passive transfluthrin-releasing device (TRD) to inhibit Ae. aegypti oviposition; 3) To evaluate a push-pull system consisting of an oviposition inhibitor (TRD) and the Gravid Aedes Trap (GAT) to promote mass Ae. aegypti capture in Piumhi-MG. Material and Methods: 1) In the laboratory, gravid Ae. aegypti were exposed to different transfluthrin concentrations (0, 2, 5, 10 and 15%) for 1 minute. 2) In semi-field and field, jute strips (10 x 15cm) impregnated with the same transfluthrin concentrations of the previous experiment were placed in ovitraps (10L), filled with water (approximately 2L) and an oviposition substrate. The effect of the jute strip sizes (150, 300 and 450cm2) and the TRD positioning at different heights in relation to the edge of the ovitraps (0, 10, 25 and 50cm) on Ae. aegypti oviposition were also evaluated under semi-field conditions. 3) A push-pull system composed by oviposition inhibitor (n=220) and the GAT (n=352) was compared to an area with only suppression GAT (n=320) and to a control area (n =27 monitoring GATs). Results and Conclusions: 1) Between the two Ae. aegypti strains evaluated, approximately 39% of the exposed mosquitoes were verified in knockdown 1 hour after exposure and 41% died after 24 hours. Transfluthrin inhibited oviposition in exposed females. The biological parameters egg viability, larval period, sex ratio and wing size were also affected at different levels by transfluthrin exposure. 2) The Ae. aegypti oviposition inhibition by the TRD was observed in all concentrations in relation to the control (jute strip without transfluthrin) in semi-field and field conditions. The TRD configuration that presented greater inhibition of Ae. aegypti oviposition consisted of jute strips (450cm2) impregnated with transfluthrin (5%) and positioned on the inner wall of ovitraps. 3) The push-pull system caused a slight decrease (33%) in Ae. aegypti population of the area. However, with only one trap/house in 50% of the intervention areas properties, was verified a general decrease of approximately 54% of the mosquito population in the study areas. The TRD had low cost, easy production, handle and can be applied in large-scale studies. It was verified mass Ae. aegypti suppression with GAT in Piumhi city.